Highly stretchable gelatin‐polyacrylamide hydrogel for potential transdermal drug release. Issue 1 (30th October 2020) - Qiao, Zhen; Tran, Long; Parks, Jesse; Zhao, Yao; Hai, Nan; Zhong, Yinghui; Ji, Hai‐Feng
Abstract: Stretchable hydrogels have been used for a number of biomedical applications. This research focused on the study of a highly stretchable and tough hydrogel made of gelatin and polyacrylamide towards transdermal drug delivery applications. Four drug compounds, nicotine, lidocaine hydrochloride, diltiazem hydrochloride and diclofenac sodium, were used for the evaluation. The release rates of these compounds follow an order: lidocaine > diltiazem > nicotine > diclofenac, which showed a strong correlation between the release rate with their solubility in water at pH 5.5. The kinetics study showed a linear and sustainable release of all tested drugs in the first 8 hours. Experiments were conducted in vitro on replicated human skin. Cytotoxicity studies indicate hydrogel is nontoxic to human cells. The highly stretchable and tough characters of the hydrogel the strength of the hydrogel reduce the severity of wear and tear issues over time for transdermal drug release. Abstract : This research focused on the study of a highly stretchable and tough hydrogel made of gelatin and polyacrylamide towards transdermal drug delivery applications. The release rates of these compounds follow an order: lidocaine>diltiazem>nicotine>diclofenac, which showed a strong correlation between the release rate with their solubility in water at pH 5.5 and their interactions with the gel network.